Peralihan Hak Atas Tanah melalui Putusan Pengadilan: Implikasi Yuridis dan Tantangan dalam Pelaksanaan - Laila Nuraini; Yunanto Yunanto (SIGn Jurnal Hukum, 2023)
This study aims to examine and analyze the juridical implications of land rights transfers through court decisions and identify the challenges and obstacles encountered in transferring them. This study uses normative legal research with conceptual, case, and comparative approaches. The collected legal material is then qualitatively analyzed to describe the problem and answer study purposes. The results show that the dispute resolution of land rights transfers through inkracht court decisions can provide legal certainty and positive impacts for the disputing parties. However, some negative effects need to be anticipated and managed effectively. Furthermore, challenges and obstacles are faced when executing land rights transfers based on inkracht court decisions, necessitating efforts to improve the court decision enforcement system. Improving the court decision enforcement system involves the active participation of the government, law enforcement, land agencies, and parties involved in land rights transfer disputes. Therefore, it is recommended that parties involved in land rights transfer disputes consider the negative impacts of inkracht court decisions by collaborating with law enforcement. Through good cooperation and coordination among agencies and enhanced law enforcement capacity, it is hoped that the land rights dispute resolution system transfer can create legal certainty and promote the economic value growth of disputed land, ultimately impacting the productivity and welfare of the surrounding community.